An initial assessment of observations from the Suomi‐NPP satellite: data from the Cross‐track Infrared Sounder (CrIS). (5th January 2015) - Smith, Andrew; Atkinson, Nigel; Bell, William; Doherty, Amy
Abstract This paper gives an appraisal of the hyperspectral Cross‐track Infrared Sounder (CrIS) on board the Suomi‐NPP satellite, for use in numerical weather prediction (NWP) at the Met Office. The quality of CrIS data is assessed by comparison with short‐range NWP forecasts, and the impact on forecasts is evaluated using results from assimilation experiments. The impact of assimilating CrIS and the complementary microwave sounder ATMS (Advanced Technology Microwave Sounding Unit) together is also presented.